Changes in Norisoprenoid Levels with Long-term Nitrogen Fertilisation in Different Vintages of Vitis vinifera var. Riesling Wines - Linsenmeier, A.W.; Löhnertz, O. (South African Journal of Enology and Viticulture, 2016)
C13-norisoprenoids were measured in Riesling wines produced from the 1996, 1997 and 2003 vintages within the scope of a long-term nitrogen (N) fertilisation experiment. The wines were made from treatments of 0, 60 and 150 kg N/ha; each treatment was repeated four times and arranged in a completely randomised design. N fertilisation led to lower TDN (1,1,6-trimethyl-1,2-dihydronaphthalene) concentrations, whereas the trend was for actinidol and ß-damascenone to increase with increasing fertilisation and vitispirane was not affected by fertilisation. Yield, which was affected by N fertilisation, showed negative correlations with norisoprenoids in 1996 and 1997. Vitispirane, actinidol and TDN increased with storage time. The colder year, 1996, which had fewer sunshine hours, resulted in higher concentrations of ß-damascenone and lower concentrations of the norisoprenoids vitispirane, actinidol and TDN compared with 1997.